PREVALENCE OF ENTAMOEBA HISTOLYTICA AND GIARDIA LAMBLIA IN CHILDREN IN DUHOK PROVINCE, KURDISTAN REGION, IRAQ - HAJI, HILEEN MUSTAFA; BAMARNI, SHAMEERAN SALMAN ISMAEL (Journal of Duhok University, 2023)
Objective: Entamoeba histolytica and Giardia lamblia are common serious public health problems in children in developing countries. The purpose of this study was to determine the prevalence of these parasites among children in Duhok Province, Kurdistan region, Iraq. Six hundred stool samples were collected from children of both sexes and different age groups from ages 2-12 years living in Duhok city and some nearby villages, who visited an outpatient clinic (Hevi Pediatric Hospital) and some Private Laboratories (Vin Private laboratory and Sardam Private laboratory), Iraqi Kurdistan, during the period from June – November of 2021.The samples were examined microscopically by both direct and flotation methods for detection of both parasites including Entamoeba histolytica and Giardia lamblia. Results: The prevalence of Entamoeba histolytica and Giardia lamblia among the 600 children were 47.66% -15.55%, respectively. The highest rate of both Amoebiasis and Giardiasis was found in children that the origin of the drinking water was tap water at a rate of 83.0% and the lower rate was in children that the origin of the drinking water was distilled water at 17.0%. This suggests that gastrointestinal parasites continue to be a public health concern in areas where sanitation and hygiene measures are narrow. A significant difference was shown between the females and males in both cases (Amoebiasis and Giardiasis) at a P value > 0.05. In the case of Amoebiasis the infection rate was higher in females than in males (69.9 %, 30.1%).) respectively. Also in the case of Giardiasis was higher in females than males respectively (64.5%, 35.5%) this difference was statistically significant at a P<0.05. This suggested that these two intestinal parasites remain a challenging public health concern wherever sanitation and health measures are inadequate. In conclusion: Urgent steps, such as long-term control measures and the improvement of personal hygiene practices, as well as sanitary and living conditions, must be taken